Um olhar sobre a cena do graffiti no Rio de Janeiro - Leal, Ana Lucia Peres (2009)
In this work, through an etnography, it was intended to understand what is this called by the young grafiteiros as graffiti scene in Rio de Janeiro. The analysis of the established social relations between them was observed having in mind the relation graffiti/ pixação . The social trajectories of some of these social actors had been analyzed to elucidate the forms of access to this practical, as well as some forms of transmission of knowing necessary for the conformation of the grafiteiro identification. Moral values and rules that conduct the behavior had been observed leading to consider a fluidity enter practical of the graffiti and the pixação , through the manipulation of identifications